2021
DOI: 10.3390/microorganisms9040689
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Southern Tomato Virus (STV) Interacts with Cucumber Mosaic and/or Pepino Mosaic Virus in Mixed- Infections Modifying Plant Symptoms, Viral Titer and Small RNA Accumulation

Abstract: Southern tomato virus (STV) is a persistent virus that was, at the beginning, associated with some tomato fruit disorders. Subsequent studies showed that the virus did not induce apparent symptoms in single infections. Accordingly, the reported symptoms could be induced by the interaction of STV with other viruses, which frequently infect tomato. Here, we studied the effect of STV in co- and triple-infections with Cucumber mosaic virus (CMV) and Pepino mosaic virus (PepMV). Our results showed complex interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…Axenic chickens infected with Marek’s disease virus had more severe disease ( 93 ). Similar enhancements can happen in plants, as plants persistently infected with Southern tomato virus develop stronger symptoms when infected with pathogenic viruses, such as cucumber mosaic and pepino mosaic viruses ( 94 ).…”
Section: Microbiome-mediated Enhancement Of Viral Infectionsmentioning
confidence: 84%
“…Axenic chickens infected with Marek’s disease virus had more severe disease ( 93 ). Similar enhancements can happen in plants, as plants persistently infected with Southern tomato virus develop stronger symptoms when infected with pathogenic viruses, such as cucumber mosaic and pepino mosaic viruses ( 94 ).…”
Section: Microbiome-mediated Enhancement Of Viral Infectionsmentioning
confidence: 84%
“…This suggests that XYDV could interfere with root development and plant growth in seedlings when XYCV concentration surpasses a certain threshold. A positive correlation between symptoms and viral accumulation has been also reported for several plant viruses [ 17 , 18 , 19 ], although this does not apply to tolerant hosts [ 20 ]. The correlation among XYDV accumulation and symptom manifestation, as well as the fact that XYDV was the only viral sequence found using HTS strongly supports that XYDV is the causal agent of the disease of leaf yellow mosaic and dwarfism in C. esculentus .…”
Section: Discussionmentioning
confidence: 95%
“…The biological role of p42 remains unclear; it has been suggested that it is the STV capsid protein, but virions have been never observed and no homologies with other viral capsid proteins have been found [6]. Moreover, recent studies showed that p42 has no RNA silencing suppressor activity [4]. Differences in the purifying selection pressure in both p42 overlapping and non-overlapping regions found in RdRp, with stronger pressure in the first one, reinforce the hypothesis of the in vivo expression of p42-although its biological function remains unknown.…”
Section: Natural Selection and Recombination Analysismentioning
confidence: 99%
“…Some of them, such as the white clover cryptic virus 1 (WCCV-1) and curvularia thermal tolerance virus (CThTV), establish symbiotic relationships with their hosts [2,3]. Nevertheless, recent studies have shown that southern tomato virus (STV), a persistent virus infecting tomato (Solanum lycopersicum), interacts with cucumber mosaic virus (CMV) and pepino mosaic virus (PepMV) in mixed infections by increasing the pathogenic effect of these viruses [4]. Besides this, the presence of STV-induced changes with the accumulation of some regulatory micro-RNAs (miRNAs) that target plant genes involved in essential plant processes such as plant development and responses to biotic or abiotic stress [4,5].…”
Section: Introductionmentioning
confidence: 99%